La caída del reino visigodo en las Antigüedades de España de Alfonso de Palencia - Francisco Bautista (Atalaya)
This paper presents an analysis of the last section of Alfonso de Palencia's Antigüedades de España, devoted to the reign of King Rodrigo and the Islamic conquest of Hispania. It focuses the diversity and quality of the sources used by the historian, in the use he makes of them, and in his historical representation of the last Visigoth king. The sources used are characterized by their small number and lack of selection among them, as well as by the distance taken by the author towards them. The vision of the period, on the other hand, doesn’t aim to present the Visigothic dynasty as a model, but, on the contrary, as a barbarian people who contributed to the decadence of Roman Hispania.